A case of mistaken identity: Charles Lillywhite, painter-decorating, and New Zealand’s gaol regulations - McCarthy, Christine (Architectural History Aotearoa, 2025)
In November 1900, American painter and decorator Charles Lillywhite was arrested at the corner of Willis and Manners Sts in Wellington after being identified as murderer Arthur Blatch while painting a postal pillar box. Blatch had murdered Alfred Welch in Colchester, England seven years earlier in December 1893. The arrest was sensational news. Multiple witnesses testified to Lillywhite being Blatch, including an Invercargill man who had known Blatch in England. In his defence Lillywhite produced a certificate of membership of the Painters’ and Decorators’ Brotherhood of North America to demonstrate he had been in America when the murder occurred, and the Chief of Police at Tacoma, Washington provided "statements from reputable citizens" identifying Lillywhite as being a resident painter and decorator in Tacoma from 1883 until 1894 when he moved to New Zealand. After four months remanded in The Terrace Gaol, Lillywhite was extradited to England, where 30 witnesses were unable to positively identify him as Blatch and he was released in late June 1901. Even before Lillywhite’s name was cleared, the Justice Department decided to revise the gaol regulations "[i]n consequence of the agitation which has arisen through the treatment of Lillywhite" to "provide for different treatment of persons awaiting trial from those under sentence." This paper examines the life and career of painter-decorator Charles Lillywhite and the gaol regulations in place in the 1900s and their consequences and implications for the interiors of New Zealand gaols.